PENGARUH PERPUTARAN MODAL KERJA TERHADAP TINGKAT LIKUIDITAS PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI PERIODE 2009-2013 - Diarni Junita Junita; Sri Kartikowati Kartikowati; Makhdalena ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of rotation of working capital to the level of liquidity in the property companies listed on the Indonesia Stock Exchange 2009-2013 period. The population in this study are property firms listed on the Indonesia Stock Exchange in 2009-2013, amounting to 13 companies. The data is secondary data obtained in the form of data that have been published and available in the company. Data is analysed using simple linear regression.The results of this study concluds that: working capital turnover and significant effect on the level of liquidity of property companies listed on the Indonesia Stock Exchange 2009-2013 period as measured by the current ratio and quick ratio. But if liquidity is measured by the ratio of cash, working capital turnover no effect. It is known that the turnover of working capital negatively affect the company's liquidity level, meaning that with the increase in working capital turnover will decrease the liquidity of the company and vice versa. Advice can be given that the company is expected to run or control the level of liquidity and working capital turnover of the company, because it is very useful to measure the performance of companies during a certain period, which is expected to provide evaluation and policy analysis for the determination of the next period.Keywords: working capital turnover, liquidity levels.